Superplastic Mg-Ni-Gd alloy and its preparation process
Patent Information
- Application Number
- CN202510595961.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-05-09
AI Technical Summary
稀土元素属于稀有金属,其开采、提炼成本较高,大量添加稀土元素会导致合金的生产成本显著增加,不利于镁合金的大规模工业化生产和广泛应用
[0028]1、本发明提出了一种强塑性Mg-Ni-Gd合金及其制备工艺,通过在镁合金中引入Ho元素,并结合热挤压和热处理工艺,对合金中的长周期堆垛有序相(LPSO相)进行有效调控。重稀土元素Ho可有效抑制镁合金晶粒长大,细化晶粒,提高合金强度和塑性,本发明通过镁合金中加入稀土元素Ho,在838K下Ho在镁基体中的固溶度可达到5.44at.%,可产生良好的固溶强化效果,同时还能促进合金中形成更多LPSO相,达到调控镁合金中LPSO相微观组织形貌的目的,从而提高Mg-Ni-Gd镁合金综合力学性能,成功制备出高强塑性的镁合金,其屈服强度达到390MPa,抗拉强度达到350MPa,延伸率达到了11.2%。这一工艺充分利用了Ho元素的特性与先进加工技术的协同作用,为镁合金性能的提升提供了全新的解决方案。
Smart Images

Figure CN120366611B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metallic materials technology and relates to a strong and ductile Mg-Ni-Gd alloy and its preparation process. Background Technology
[0002] Magnesium alloys are currently the lightest structural materials used in engineering applications (density 1.74 g / cm³). 3 Magnesium alloys, with their significant advantages such as high specific strength and high specific stiffness, have shown extremely broad application prospects in many fields such as aerospace, automotive manufacturing, and electronics. However, the relatively low absolute strength and poor room temperature plasticity of magnesium alloys greatly limit their further promotion and application in more scenarios. In view of this, the development of magnesium alloy materials with higher strength and plasticity has become a highly anticipated hot topic and key direction in the field of magnesium alloy research.
[0003] Alloying is one of the effective methods to improve the strength and plasticity of magnesium alloys. Alloying refers to the process of adding other elements to an alloy to effectively enhance its comprehensive mechanical properties, making it an alloy with the expected performance. In the research process of magnesium alloy alloying, the addition of rare earth elements has been proven to be an effective strengthening method. Rare earth elements can produce good solid solution strengthening and grain refinement strengthening effects, effectively improving the microstructure of magnesium alloys and enhancing their performance. Adding rare earth (RE) elements to magnesium alloys containing transition metal (TM) elements can generate a large number of long-period ordered packed (LPSO) phases. LPSO phases have significant advantages in terms of high strength and high elastic modulus, and can bear part of the external load, thus improving the strength of the alloy. In addition, the LPSO phase has coherence with the α-Mg matrix interface, increasing the interfacial shear stress of the magnesium alloy matrix, activating the slip of pyramidal dislocations, and at the same time, the LPSO phase has the ability to coordinate deformation, which can reduce the initiation and propagation of cracks from the source, working together to improve the plasticity of magnesium alloys.
[0004] Although the addition of rare earth elements has improved the strength and ductility of magnesium alloys to some extent, this technology still faces several unresolved issues. Firstly, the amount of rare earth elements added is typically large. Rare earth elements are rare metals with high mining and refining costs; adding large amounts significantly increases the production cost of the alloy, hindering large-scale industrial production and widespread application of magnesium alloys. Secondly, in Mg-Ni-Gd alloys, not all Ni and Gd atoms exist in the LPSO phase; some Ni forms a Mg2Ni eutectic phase with α-Mg, while Gd atoms are dispersed within the α-Mg matrix phase. This affects the stability and repeatability of magnesium alloy properties, limiting further performance improvements.
[0005] Therefore, how to improve the precise control of the LPSO phase to achieve better performance of magnesium alloys has become an important challenge in the current field of magnesium alloy research, and it is also the key problem that this patent application aims to solve. Summary of the Invention
[0006] In view of this, the purpose of the present invention is to provide a strong and ductile Mg-Ni-Gd alloy and its preparation process. Rare earth microalloying is used to improve the microstructure of the alloy and enhance the comprehensive mechanical properties of the magnesium alloy. Based on the Mg-Ni-Gd magnesium alloy, trace amounts of Ho are added to it. Through alloying, hot extrusion deformation and heat treatment processes, the quantity, distribution and morphology of the LPSO phase in the magnesium alloy are controlled to improve the microstructure of the magnesium alloy and enhance its strength and ductility.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] A process for preparing a high-ductility Mg-Ni-Gd alloy includes the following steps:
[0009] (1) Smelting: Pure magnesium, Mg-25Ni master alloy, Mg-30Gd master alloy and Mg-20Ho master alloy are smelted into alloy ingots;
[0010] (2) Homogenization annealing: The alloy ingot is wrapped with aluminum foil, then graphite powder is used to embed it in the crucible, and the crucible is placed in the heat treatment furnace. Then the temperature is raised to 525℃ and held for 12 hours. After the holding time is completed, it is cooled with water.
[0011] (3) Hot extrusion: The homogenized and annealed alloy ingot is processed into a billet, which is preheated together with the die, and then loaded into the extrusion cylinder for positive extrusion to obtain the sample. The extrusion parameters are: extrusion temperature 450℃, extrusion speed 1.5-2.5m·min -1 The extrusion ratio is 16:1, and the material is water-cooled after extrusion.
[0012] (4) Aging treatment: After the hot-extruded sample is processed to the specified size, it is wrapped with aluminum foil and then buried in the crucible with graphite powder. The crucible is placed in a heat treatment furnace and kept at 220°C for 46 hours. After the heat treatment is completed, it is cooled with water.
[0013] Further, step (1) includes the following steps:
[0014] a) Alloy raw material preparation: Grind off the oxide film on the surface of pure magnesium, Mg-25Ni master alloy, Mg-30Gd master alloy and Mg-20Ho master alloy;
[0015] b) Smelting alloys: Place pure magnesium in a crucible and place the crucible in an electric resistance furnace. Introduce a protective atmosphere of SF6+CO2. After the pure magnesium melts, add Mg-25Ni, Mg-30Gd and Mg-20Ho master alloys in sequence.
[0016] c) Stirring and impurity removal: After the alloy is completely melted, filter out the impurities. Then stir the magnesium alloy melt every 5 minutes for 3 minutes each time, for a total of 4 times. After the stirring operation is completed, keep it at the temperature for 5 minutes.
[0017] d) Cooling: Turn off the power to the resistance furnace, remove the crucible and place it in cold water to cool to room temperature, remove the alloy ingot, and continuously introduce a protective atmosphere of SF6+CO2 above the crucible during the cooling process.
[0018] Furthermore, in step (1)a), the purity of the pure magnesium is 99.99 wt.%.
[0019] Further, in step (1)b), the volume ratio of the protective atmosphere SF6+CO2 is 1:99.
[0020] Further, in step (1)c), a long-handled strainer is used to filter out impurities.
[0021] Furthermore, in step (3), the preheating temperature of the mold and the blank is 450°C, and the preheating time is 2 hours.
[0022] Furthermore, in step (3), the homogenized annealed alloy ingot is processed into a cylindrical billet;
[0023] In step (4), the hot-extruded bar is cut into cylindrical bars.
[0024] Furthermore, the atomic percentages of each element in the alloy composition of the alloy ingot are as follows: Ni: 0.75%, Gd: 1.0%, Ho: 0.1-0.2%, with the remainder being Mg.
[0025] On the other hand, the present invention also provides a strong and ductile Mg-Ni-Gd alloy, which is prepared by the aforementioned process, and the atomic percentage of each element in the alloy composition is as follows: Ni: 0.75%, Gd: 1.0%, Ho: 0.1-0.2%, and the remainder is Mg.
[0026] Furthermore, the atomic percentages of each element in its alloy composition are as follows: Ni: 0.75%, Gd: 1.0%, Ho: 0.2%, and the remainder is Mg.
[0027] The beneficial effects of this invention are as follows:
[0028] 1. This invention proposes a high-strength and ductile Mg-Ni-Gd alloy and its preparation process. By introducing Ho element into the magnesium alloy and combining hot extrusion and heat treatment processes, the long-period stacked ordered phase (LPSO phase) in the alloy is effectively controlled. The heavy rare earth element Ho can effectively inhibit grain growth in magnesium alloys, refine the grains, and improve the alloy's strength and ductility. This invention, by adding Ho to the magnesium alloy, achieves a solid solubility of 5.44 at.% in the magnesium matrix at 838 K, resulting in good solid solution strengthening. Simultaneously, it promotes the formation of more LPSO phases in the alloy, achieving the goal of controlling the microstructure morphology of the LPSO phase in the magnesium alloy, thereby improving the comprehensive mechanical properties of the Mg-Ni-Gd magnesium alloy. A high-strength and ductile magnesium alloy with a yield strength of 390 MPa, a tensile strength of 350 MPa, and an elongation of 11.2% is successfully prepared. This process fully utilizes the synergistic effect of the properties of Ho element and advanced processing technology, providing a novel solution for improving the performance of magnesium alloys.
[0029] 2. Ho plays multiple important roles in this technical solution. First, as a heavy rare earth element, Ho has a high solid solubility in magnesium alloys (approximately 5.44 at.%), promoting the formation of more LPSO phases. After adding Ho, the strength of the alloy is significantly improved through three mechanisms: solid solution strengthening, second-phase strengthening, and grain refinement strengthening. Second, by adding trace amounts of Ho, this invention reduces the Gd content to only 1.0 at.%, while achieving the same alloying effect as adding large amounts of Gd, significantly reducing the need for large amounts of rare earth elements and thus significantly lowering the production cost of magnesium alloys. This strategy not only improves performance but also achieves economic benefits, laying the foundation for the large-scale application of magnesium alloys.
[0030] 3. The innovation of this technical solution lies in the precise control of the LPSO phase using Ho element, breaking through the bottleneck between traditional magnesium alloy strength improvement and cost control. By controlling the quantity and distribution of the LPSO phase, the alloy strength is significantly improved; simultaneously, the design of reducing Gd element usage effectively optimizes the cost structure. The uniqueness of this method lies in its ability to enhance the mechanical properties of magnesium alloys while simultaneously increasing their application potential in aerospace, automotive manufacturing, and other fields. The practicality of the process is not only reflected in its dual advantages of performance and cost but also in its strong operability and ease of industrialization. This innovative and practical technical solution opens up new avenues for the development and application of high-strength magnesium alloys and has broad market prospects.
[0031] Other advantages, objectives, and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination, or may be learned from practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description
[0032] To make the objectives, technical solutions, and advantages of the present invention clearer, the preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings, wherein:
[0033] Figure 1 The tensile stress-strain curves of the magnesium alloys in Example 1 and Comparative Example 1 are shown.
[0034] Figure 2 The figures show the microstructures of magnesium alloys in Example 1 and Comparative Example 1, where the grayish-white phase is the LPSO phase; Figure (a) is Comparative Example 1 and Figure (b) is Example 1. Detailed Implementation
[0035] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of the present invention. Unless otherwise specified, the following embodiments and features can be combined with each other.
[0036] The accompanying drawings are for illustrative purposes only and are schematic diagrams, not actual images. They should not be construed as limiting the invention. To better illustrate the embodiments of the invention, some parts in the drawings may be omitted, enlarged, or reduced, and do not represent the actual product dimensions. It is understandable to those skilled in the art that some well-known structures and their descriptions may be omitted in the drawings.
[0037] In the accompanying drawings of the embodiments of the present invention, the same or similar reference numerals correspond to the same or similar components. In the description of the present invention, it should be understood that if terms such as "upper," "lower," "left," "right," "front," and "rear" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, they are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the terms used to describe positional relationships in the drawings are only for illustrative purposes and should not be construed as limiting the present invention. For those skilled in the art, the specific meaning of the above terms can be understood according to the specific circumstances.
[0038] A process for preparing a high-ductility Mg-Ni-Gd alloy includes the following steps:
[0039] (1) Smelting: Pure magnesium, Mg-25Ni master alloy, Mg-30Gd master alloy and Mg-20Ho master alloy are smelted into alloy ingots;
[0040] (2) Homogenization annealing: The alloy ingot is wrapped with aluminum foil, then graphite powder is used to embed it in the crucible, and the crucible is placed in the heat treatment furnace. Then the temperature is raised to 525℃ and held for 12 hours. After the holding time is completed, it is cooled with water.
[0041] (3) Hot extrusion: The homogenized and annealed alloy ingot is processed into a billet, which is preheated together with the die, and then loaded into the extrusion cylinder for positive extrusion to obtain the sample. The extrusion parameters are: extrusion temperature 450℃, extrusion speed 1.5-2.5m·min -1 The extrusion ratio is 16:1, and the material is water-cooled after extrusion.
[0042] (4) Aging treatment: After the hot-extruded sample is processed to the specified size, it is wrapped with aluminum foil and then buried in the crucible with graphite powder. The crucible is placed in a heat treatment furnace and kept at 220°C for 46 hours. After the heat treatment is completed, it is cooled with water.
[0043] Further, step (1) includes the following steps:
[0044] a) Alloy raw material preparation: Grind off the oxide film on the surface of pure magnesium, Mg-25Ni master alloy, Mg-30Gd master alloy and Mg-20Ho master alloy;
[0045] b) Smelting alloys: Place pure magnesium in a crucible and place the crucible in an electric resistance furnace. Introduce a protective atmosphere of SF6+CO2. After the pure magnesium melts, add Mg-25Ni, Mg-30Gd and Mg-20Ho master alloys in sequence.
[0046] c) Stirring and impurity removal: After the alloy is completely melted, filter out the impurities. Then stir the magnesium alloy melt every 5 minutes for 3 minutes each time, for a total of 4 times. After the stirring operation is completed, keep it at the temperature for 5 minutes.
[0047] d) Cooling: Turn off the power to the resistance furnace, remove the crucible and place it in cold water to cool to room temperature, remove the alloy ingot, and continuously introduce a protective atmosphere of SF6+CO2 above the crucible during the cooling process.
[0048] Furthermore, in step (1)a), the purity of the pure magnesium is 99.99 wt.%.
[0049] Further, in step (1)b), the volume ratio of the protective atmosphere SF6+CO2 is 1:99.
[0050] Further, in step (1)c), a long-handled strainer is used to filter out impurities.
[0051] Furthermore, in step (3), the preheating temperature of the mold and the blank is 450°C, and the preheating time is 2 hours.
[0052] Furthermore, in step (3), the homogenized annealed alloy ingot is processed into a cylindrical billet;
[0053] In step (4), the hot-extruded bar is cut into cylindrical bars.
[0054] Furthermore, the atomic percentages of each element in the alloy composition of the alloy ingot are as follows: Ni: 0.75%, Gd: 1.0%, Ho: 0.1-0.2%, with the remainder being Mg.
[0055] A strong and ductile Mg-Ni-Gd alloy was prepared by the above-mentioned process. The atomic percentage of each element in the alloy composition is as follows: nickel (Ni): 0.75%, gadolinium (Gd): 1.0%, holmium (Ho): 0.1-0.2%, with the remainder being magnesium and other unavoidable impurities.
[0056] The principle behind the Ni / Gd element ratio design in this application is that when the atomic percentages of Ni and Gd are 3:4, the LPSO phase in the alloy is most abundant and most dispersed. The principle behind adding Ho is that the heavy rare earth element Ho can effectively inhibit grain growth in magnesium alloys, refine the grains, and improve the alloy's strength and plasticity. Adding Ho to magnesium alloys allows for a solid solubility of 5.44 at.% in the magnesium matrix at 838 K, resulting in good solid solution strengthening. Simultaneously, it promotes the formation of more LPSO phases in the alloy, achieving the goal of controlling the microstructure morphology of the LPSO phase in the magnesium alloy, thereby improving the comprehensive mechanical properties of the Mg-Ni-Gd magnesium alloy.
[0057] Example 1
[0058] The technical solution of this embodiment is as follows:
[0059] (1) In terms of atomic percentage, the elemental composition of the strong plastic Mg-Ni-Gd alloy in this embodiment includes: Ni: 0.75%, Gd: 1.0%, Ho: 0.2%, and the balance is Mg.
[0060] The preparation method of the strong and ductile Mg-Ni-Gd alloy in this embodiment includes the following process:
[0061] 1) Smelting:
[0062] a) Using pure magnesium ingots (99.99 wt.%) and three intermediate alloys, Mg-25Ni (wt.%), Mg-30Gd (wt.%) and Mg-20Ho (wt.%), as raw materials, the materials were batched according to the alloy design composition. Before smelting, the surfaces of the magnesium ingots and intermediate alloys were polished with a grinding wheel or sandpaper to remove stains and oxide scale from the surface of the raw materials. Then, they were rinsed with anhydrous ethanol and dried.
[0063] b) Prepare a release coating using anhydrous ethanol and boron nitride, apply it evenly to the inner surface of a steel crucible, dry it, place the pure magnesium ingot into the crucible, and then place it in a resistance furnace. Set the temperature of the resistance furnace to 730℃, and introduce V current directly above the crucible. SF6 :V CO2 A 1:99 gas mixture is used as a protective atmosphere to ensure that the molten metal inside the crucible is essentially isolated from the air.
[0064] c) After the pure magnesium ingots in the crucible have completely melted, use tongs to add the dried intermediate alloy into the crucible in sequence (when adding materials, turn off the power of the resistance furnace to prevent short circuits, and turn the power of the resistance furnace back on after adding materials); since there is a certain deviation between the temperature displayed by the resistance furnace and the actual temperature of the molten metal, insert a thermocouple into the molten metal to observe the temperature change of the molten metal in the crucible at any time.
[0065] d) After the alloy in the crucible has completely melted, use a long-handled strainer to remove the oxides from the surface of the molten alloy. Then, stir the magnesium alloy melt with an electric stirrer every 5 minutes, each stirring lasting 3 minutes, for a total of 4 times. After stirring the molten metal in the crucible, keep it at the desired temperature for 5 minutes.
[0066] e) Turn off the power to the resistance furnace, remove the crucible, and quench it in water. During the cooling and solidification of the melt, move the protective atmosphere gas pipe to ensure that the protective atmosphere is continuously supplied above the crucible until the alloy ingot is completely solidified.
[0067] 2) Homogenization annealing: The alloy ingot obtained from smelting is wrapped with aluminum foil and then completely buried in a stainless steel crucible with graphite powder. The crucible is placed in a heat treatment furnace. The homogenization annealing process is: 525℃×12h, and the cooling method is water cooling.
[0068] 3) Hot extrusion: The homogenized annealed alloy ingot is processed into a cylindrical billet with a diameter of 80mm. After preheating the billet and the mold at 450℃ for 2 hours, it is placed into the extrusion cylinder for positive extrusion. The extrusion parameters are: extrusion temperature: 450℃, extrusion speed: 1.5-2m·min. -1 Extrusion ratio: 16:1, water-cooled after extrusion.
[0069] 4) Aging treatment: Cut the bar obtained after hot extrusion into cylindrical bars with a length of 70mm. Wrap the cut bars with aluminum foil and then bury them completely in a stainless steel crucible with graphite powder. Place the crucible in a heat treatment furnace. Aging process: 220℃×46h, cooling method: water cooling.
[0070] (3) The yield strength of the alloy was 390 MPa, the tensile strength was 350 MPa, and the elongation was 11.2% as measured by a room temperature tensile mechanical property testing machine.
[0071] Comparative Example 1:
[0072] The technical solution for this comparative example is as follows:
[0073] (1) The elemental composition of the magnesium alloy in this comparative example, by atomic percentage, includes: Ni: 0.75%, Gd: 1.0%, with the balance being Mg.
[0074] The preparation method of this comparative magnesium alloy includes the following steps:
[0075] 1) Smelting:
[0076] a) Using pure magnesium ingots (99.99 wt.%) and two intermediate alloys, Mg-25Ni (wt.%) and Mg-30Gd (wt.%), as raw materials, the materials were batched according to the alloy design composition. Before smelting, the surfaces of the magnesium ingots and intermediate alloys were polished with a grinding wheel or sandpaper to remove stains and oxide scale from the surface of the raw materials. Then, they were rinsed with anhydrous ethanol and dried.
[0077] b) Prepare a release coating using anhydrous ethanol and boron nitride, apply it evenly to the inner surface of a steel crucible, dry it, place the pure magnesium ingot into the crucible, and then place it in a resistance furnace. Set the temperature of the resistance furnace to 730℃, and introduce V current directly above the crucible. SF6 :V CO2 A 1:99 gas mixture is used as a protective atmosphere to ensure that the molten metal inside the crucible is essentially isolated from the air.
[0078] c) After the pure magnesium ingots in the crucible have completely melted, use pliers to add the dried intermediate alloy into the crucible in sequence; since there is a certain deviation between the temperature displayed by the resistance furnace and the actual temperature of the molten metal, insert a thermocouple into the molten metal so as to observe the temperature change of the molten metal in the crucible at any time.
[0079] d) After the alloy in the crucible has completely melted, use a long-handled strainer to remove the oxides from the surface of the molten alloy. Then, stir the magnesium alloy melt with an electric stirrer every 5 minutes, each stirring lasting 3 minutes, for a total of 4 times. After stirring the molten metal in the crucible, keep it at the desired temperature for 5 minutes.
[0080] e) Turn off the power to the resistance furnace, remove the crucible, and quench it in water. During the cooling and solidification of the melt, move the protective atmosphere gas pipe to ensure that the protective atmosphere is continuously supplied above the crucible until the alloy ingot is completely solidified.
[0081] 2) Homogenization annealing: The alloy ingot obtained from smelting is wrapped with aluminum foil and then completely buried in a stainless steel crucible with graphite powder. The crucible is placed in a heat treatment furnace. The homogenization annealing process is: 525℃×12h, and the cooling method is water cooling.
[0082] 3) Hot extrusion: The homogenized annealed alloy ingot is processed into a cylindrical billet with a diameter of 80mm. After preheating the billet and the mold at 450℃ for 2 hours, it is placed into the extrusion cylinder for positive extrusion. The extrusion parameters are: extrusion temperature: 450℃, extrusion speed: 1.5-2m·min. -1 Extrusion ratio: 16:1, water-cooled after extrusion.
[0083] 4) Aging treatment: Cut the bar obtained after hot extrusion into cylindrical bars with a length of 70mm. Wrap the cut bars with aluminum foil and then bury them completely in a stainless steel crucible with graphite powder. Place the crucible in a heat treatment furnace. Aging process: 220℃×46h, cooling method: water cooling.
[0084] (3) The yield strength of the magnesium alloy was 358 MPa, the tensile strength was 316 MPa and the elongation was 8.9% as measured by a room temperature tensile mechanical property testing machine.
[0085] Table 1. Elemental composition (at%, atomic percentage) of magnesium alloys in Example 1 and Comparative Example 1.
[0086] Comparative Example 1 0.75 1.0 - margin Example 1 0.75 1.0 0.2 margin
[0087] Table 2 Tensile mechanical properties of magnesium alloys from Example 1 and Comparative Example 1
[0088] Comparative Example 1 358 316 8.9 Example 1 390 350 11.2
[0089] Please see Figures 1-2 This invention effectively controls the LPSO phase in magnesium alloys by adding Ho element and combining hot extrusion and heat treatment processes. Figure 2 The grayish-white phase is the LPSO phase. By comparison, after adding trace amounts of Ho, the amount of LPSO phase in the alloy structure increased significantly. A large number of fine lamellar LPSO phases precipitated and were evenly distributed in the magnesium matrix, which significantly improved the strength of the magnesium alloy, resulting in a high-strength and ductile magnesium alloy with a yield strength of 390 MPa, a tensile strength of 350 MPa, and an elongation of 11.2%.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A preparation process for a high-ductility Mg-Ni-Gd alloy, characterized in that, Includes the following steps: (1) Smelting: Pure magnesium, Mg-25Ni master alloy, Mg-30Gd master alloy and Mg-20Ho master alloy are smelted into alloy ingots; (2) Homogenization annealing: The alloy ingot is wrapped with aluminum foil, then graphite powder is used to embed it in the crucible, and the crucible is placed in the heat treatment furnace. Then the temperature is raised to 525℃ and held for 12 hours. After the holding time is completed, it is cooled with water. (3) Hot extrusion: The homogenized and annealed alloy ingot is processed into a billet and preheated together with the die. Then it is loaded into the extrusion cylinder for positive extrusion to obtain the sample. The extrusion parameters are: extrusion temperature 450℃, extrusion speed 1.5-2.5m·min -1 The extrusion ratio is 16:1, and the material is water-cooled after extrusion. (4) Aging treatment: After the hot-extruded sample is processed to the specified size, it is wrapped with aluminum foil, then embedded in the crucible with graphite powder, and the crucible is placed in the heat treatment furnace. Then it is kept at 220℃ for 46 hours, and then water-cooled after the heat treatment is completed. The alloy composition of the alloy ingot contains the following atomic percentages: Ni: 0.75%, Gd: 1.0%, Ho: 0.1-0.2%, with the remainder being Mg.
2. The preparation process according to claim 1, characterized in that, Step (1) includes the following steps: a) Alloy raw material preparation: Grind off the oxide film on the surface of pure magnesium, Mg-25Ni master alloy, Mg-30Gd master alloy and Mg-20Ho master alloy; b) Smelting alloys: Place pure magnesium in a crucible and place the crucible in an electric resistance furnace. Introduce a protective atmosphere of SF6+CO2. After the pure magnesium melts, add Mg-25Ni, Mg-30Gd and Mg-20Ho master alloys in sequence. c) Stirring and impurity removal: After the alloy is completely melted, filter out the impurities. Then stir the magnesium alloy melt every 5 minutes for 3 minutes each time, for a total of 4 times. After the stirring operation is completed, keep it at the temperature for 5 minutes. d) Cooling: Turn off the power to the resistance furnace, remove the crucible and place it in cold water to cool to room temperature, remove the alloy ingot, and continuously introduce a protective atmosphere of SF6+CO2 above the crucible during the cooling process.
3. The preparation process according to claim 2, characterized in that, In step (1) a), the purity of the pure magnesium is 99.99 wt.%.
4. The preparation process according to claim 2, characterized in that, In step (1)b), the volume ratio of the protective atmosphere SF6+CO2 is 1:
99.
5. The preparation process according to claim 2, characterized in that, In step (1)c), use a long-handled strainer to filter out impurities.
6. The preparation process according to claim 1, characterized in that, In step (3), the preheating temperature of the mold and the blank is 450°C and the preheating time is 2 hours.
7. The preparation process according to claim 1, characterized in that, In step (3), the alloy ingot after homogenization and annealing is processed into a cylindrical billet; In step (4), the hot-extruded bar is cut into cylindrical bars.
8. A high-ductility Mg-Ni-Gd alloy, characterized in that, The alloy is prepared by any one of the preparation processes described in claims 1-7, and the atomic percentages of each element in its alloy composition are as follows: Ni: 0.75%, Gd: 1.0%, Ho: 0.1-0.2%, with the remainder being Mg.
9. The high-ductility Mg-Ni-Gd alloy according to claim 8, characterized in that, The atomic percentages of each element in its alloy composition are: Ni: 0.75%, Gd: 1.0%, Ho: 0.2%, and the remainder is Mg.
Citation Information
Patent Citations
Nickel-containing heat resisting magnesium-rare earth alloy and preparation method thereof
CN101392345A
High-strength high-damping Mg-Gd-Ni magnesium alloy and preparation method thereof
CN114134380A